Decision Support System for Industry Machine Maintenance Using Weight Product (WP) Method - Rika Yunitarini; Ernaning Widiaswanti (TIERS Information Technology Journal, 2022)
Machine maintenance management is one of the important aspects in every industry. Implementation of machine maintenance management requires the management of various types of data such as machine age, machine condition and so on. Data management with the help of a decision support system will help improve the effectiveness and efficiency of machine maintenance management. In making the right and correct decisions, it is necessary to have decision support. Without machine maintenance management, it can harm the industry because the machine maintenance schedule cannot be determined optimally, and the costs incurred by repair, maintenance and production cessation activities cannot be determined directly. Therefore, the industry needs a decision support system that is able to improve the efficiency of its machine maintenance management. This research focuses on the design and development of a machine maintenance decision support system application using the weighted product (WP) method. Weighted product (WP) method is one of the multi criteria decision making methods used to determine the final decision by using several criteria. This method can provide a reliable methodology that helps to organize the most optimized result in the presence of many different opportunities, parameters, and constraints. Research method used in this study is the Web Engineering Method. This system is developed by using PHP programming language and MySQL as a database. This system is expected to increase the effectiveness and efficiency of machine maintenance management.